Advancements in English listening education: Chat GPT and convolutional neural network integration - Runmei Xing (Journal of Pedagogical Research, 2023)
In today's globalized world, strong English listening skills have become more essential than ever before. Whether you're a language learner, a professional conducting business internationally, or a traveler exploring new cultures, the ability to understand spoken English is an asset. Fortunately, advancements in technology have opened new avenues for enhancing our English listening skills. One cutting-edge solution that has gained attention is the Chat GPT and Convolutional Neural Network (CNN) model. This innovative approach incorporates AI technology to improve language processing and comprehension. Listening is a crucial skill in language learning as it helps students become more proficient in understanding spoken language, accents, and various forms of communication. It is essential for effective communication in real-life situations. The research findings could highlight the potential benefits of using multimedia applications for improving listening skills, contributing to a better understanding of how technology can enhance language education.